Risky lessons: sex education and social inequality - Fields, Jessica (Rutgers Series in Childhood Studies, 2008)
Curricula in U.S. public schools are often the focus of heated debate, and few subjects spark more controversy than sex education. While conservatives argue that sexual abstinence should be the only message, liberals counter that an approach that provides comprehensive instruction and helps young people avoid sexually transmitted diseases and pregnancy is necessary. Caught in the middle are the students and teachers whose everyday experiences of sex education are seldom as clear-cut as either side of the debate suggests. Risky Lessons brings readers inside three North Carolina middle schools to show how students and teachers support and subvert the official curriculum through their questions, choices, viewpoints, and reactions. Most important, the book highlights how sex education's formal and informal lessons reflect and reinforce gender, race, and class inequalities. Ultimately critical of both conservative and liberal approaches, Fields argues for curricula that promote social and sexual justice. Sex education´s aim need not be limited to reducing the risk of adolescent pregnancies, disease, and sexual activity. Rather, its lessons should help young people to recognize and contend with sexual desires, power, and inequalities.